2015
DOI: 10.1111/1365-2478.12229
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring viscosity changes from time‐lapse seismic attenuation: case study from a heavy oil reservoir

Abstract: Heating heavy oil reservoirs is a common method for reducing the high viscosity of heavy 7 oil and thus increasing the recovery factor. Monitoring of these viscosity changes in the 8 reservoir is essential for delineating the heated region and controlling production. In this 9 study, we present an approach for estimating viscosity changes in a heavy oil reservoir. The 10 approach consists of three steps: measuring seismic wave attenuation between reflections 11 from above and below the reservoir, constructing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Several subsequent studies investigated attenuation in partially saturated media [e.g., Guennou, 2012, Müller et al, 2010], and most of them confirmed the strong magnitude of attenuation as observed by Mavko and Nur [1979]. Moreover, the direct link between fluid viscosity and attenuation allowed Shabelansky et al [2015] to use the latter as a proxy to monitor the viscosity changes during the heating of heavy oil reservoirs, and hence to manage the production.…”
Section: Introductionmentioning
confidence: 85%
“…Several subsequent studies investigated attenuation in partially saturated media [e.g., Guennou, 2012, Müller et al, 2010], and most of them confirmed the strong magnitude of attenuation as observed by Mavko and Nur [1979]. Moreover, the direct link between fluid viscosity and attenuation allowed Shabelansky et al [2015] to use the latter as a proxy to monitor the viscosity changes during the heating of heavy oil reservoirs, and hence to manage the production.…”
Section: Introductionmentioning
confidence: 85%
“…More advanced imaging methods traditionally only applicable in exploration seismology (Shabelansky et al, 2014) or even medical imaging (Robert and Fink, 2008;Touma et al, 2020) can be used for passive seismology. Recently several migration methods have been developed to image subsuface discontinues with converted phases (Shabelansky et al, 2014(Shabelansky et al, , 2015Pollitz, 2019). These methods show the advantage of using just a few earthquakes and a receiver array on the surface to image subsurface structures, such as vertical faults, which are generally hard for traditional imaging methods.…”
Section: Advanced Imaging Methodsmentioning
confidence: 99%
“…In order to disentangle the source and path effects, SymAE associates the path effects to the dissimilarities among the arrivals recorded at multiple receiver stations, and the remaining similarities are identified as the source. Existing signal processing methods that extract the time-lapse attenuation changes also utilize the relative changes in the amplitude and phase spectra among various arrivals in the data (Rickett, 2007;Shabelansky et al, 2015). Bharadwaj et al (2019) proposed a blind-deconvolution algorithm, which also extracts dissimilarities in the multichannel records using focusing constraints, but assumes that the path effects are front-loaded in time.…”
Section: Time Lapse Monitoringmentioning
confidence: 99%